Determination of Employee Performance: Effects of Technology, Work Environment and Leadership Style in Gas Distribution Service Companies in Bekasi City - Wahyudi, Anang; Ali, Hapzi (Dinasti Publisher, 2024)
In this research, the author will analyze how the work environment, leadership style and communication between employees can affect employee performance in one of the natural gas distribution service companies in Bekasi city. The purpose of this research is to determine the influence of the work environment, leadership style and communication between employees on employee performance. This study used quantitative methods. (Ali, 2013). The total population in this study was 107 people, with a sample of 100 people. Sampling in this study used purposed random sampling. Furthermore, the data used in this study is primary data, which is data obtained from questionnaires that have been given to employees in the company through google form. The results of this study are: 1) Information Technology affects Employee Performance; 2) The work environment affects Employee Performance; 3) Leadership style affects employee performance 4) Information Technology, Work Environment and Leadership Style together affect Employee Performance.